Diseño y estandarización de un instrumento de desarrollo para niños con síndrome Down de 0 a 36 meses de edad cronológica de la ciudad de Bogotá. - Hewitt Ramírez, Nohelia; Rozo Sánchez, Margarita (Acta Colombiana de Psicología, 2001)
This research designed and standardized a developmental assessment instrument. It is for children with Down syndrome age birth to 36 months. The standardization study worked with 105 children from different social economical status and from different institutions (Health providers and Special Education Programs). The children had moderate mental retarded and had a genetic diagnostic, without other psychological disorders associated. The sample involved five groups per age (0-6; 7-12; 13-18; 19-24; and 25-36 months). It was used a descriptive correlation analyses. The internal consistency coefficient by Kuder- Richardson is 0.98. The instrument has for interpretation 25 norm tables per age in the psychomotor, socioaffective, communication and cognitive areas.